Dedicated high dose rate 192Ir brachytherapy radiation fields for in vitro cell exposures at variable source-target cell distances: killing of mammalian cells depends on temporal dose rate fluctuation - Veigel, Cornelia; Debus, Jürgen; Hartmann, Günther H.; Weber, Klaus-Josef (Physics in medicine and biology, 2017)
Afterloading brachytherapy is conducted by the stepwise movement of a radioactive source through surgically implanted applicator tubes where at predefined dwell positions calculated dwell times optimize spatial dose delivery with respect to a planned dose level. The temporal exposure pattern exhibits drastic fluctuations in dose rate at a given coordinate and within a single treatment session because of the discontinuous and repeated source movement into the target volume. This could potentially affect biological response. Therefore, mammalian cells were exposed as monolayers to a high dose rate 192 Ir source by utilizing a dedicated irradiation device where the distance between a planar array of radioactive source positions and the plane of the cell monolayer could be varied from 2.5 mm to 40 mm, thus varying dose rate pattern for any chosen total dose. The Gammamed IIi afterloading system equipped with a nominal 370 GBq (10 Ci) 192-Ir source was used to irradiate V79 Chinese hamster lung fibroblasts from both confluent and from exponential growth phase with dose up to 12 Gy (at room temperature, total exposure not exceeding 1 h). For comparison, V79 cells were also exposed to 6 MV x-rays from a clinical linear accelerator (dose rate of 2.5 Gy min −1 ). As biological endpoint, cell survival was determined by standard colony forming assay. Dose measurements were conducted with a diamond detector (sensitive area 7.3 mm 2 ), calibrated by means of 60 Co radiation. Additionally, dose delivery was simulated by Monte Carlo calculations using the EGSnrc code system. The calculated secondary electron fluence spectra at the cell location did not indicate a significant change of radiation quality (i.e. higher linear energy transfer) at the lower distances. Clonogenic cell survival curves obtained after brachytherapy exhibited an altered biological response compared to x-rays which was characterized by a significant reduction of the survival curve shoulder when dose rate fluctuations were high. Therefore, also for the time scale of the present investigation, cellular effects of radiation are not invariant to the temporal pattern in dose rate. We propose that with high dose rate variation the cells activate less efficiently their DNA damage response than after continuous irradiation.